Effect of Atom Interchange on Half Metallicity of AuMnSn Heusler Compound - Singh, Mukhtiyar; Singh, Hardev; K. Kashyap, Manish (Asian Journal of Chemistry, 2011)
We have studied the effect of mutual interchange of transition metal atoms on electronic and magnetic properties of AuMnSn Heulser compound using full potential linearized augmented plane wave (FPLAPW) within generalized gradient approximation (GGA). The AuMnSn compound is predicted to be nearly half metallic ferromagnet (HMF) with 72 % spin polarization whereas MnAuSn show the low value of spin polarization (21 %). We have observed lower magnetic moment in MnAuSn (3.48 μB) as compared to AuMnSn (4.01 μB) which shows the important role of local atomic environment and coordination present in the respective compound.